2020
DOI: 10.21203/rs.2.24175/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health behaviors in major chronic diseases patients: Trends and regional variations analysis, 2008–2017, Korea

Abstract: Background: Improving the health behaviors of those with chronic diseases such as hypertension and diabetes is important for disease management. Few in-depth studies have been conducted in Korea on the health behaviors of chronic disease patients. This study examined the health behaviors of chronic disease patients over time and compared them with those of the general population.Methods: Data obtained from the Korea Community Health Survey from 2008 to 2017 were analyzed. Thirteen diseases were included in thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our result is in line with a study which revealed that people with major chronic diseases did not notably show better health behaviors, and some people even showed worse health behaviors than the general population. 20 Longitudinal data from Canada indicated that modest changes were observed among people with chronic diseases. For example, smoking cessation was observed significantly among all groups of chronic health conditions, yet a large portion of smokers did not quit at all.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is in line with a study which revealed that people with major chronic diseases did not notably show better health behaviors, and some people even showed worse health behaviors than the general population. 20 Longitudinal data from Canada indicated that modest changes were observed among people with chronic diseases. For example, smoking cessation was observed significantly among all groups of chronic health conditions, yet a large portion of smokers did not quit at all.…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 1277 titles/abstracts were screened; of these, 192 full‐text articles were assessed. Of the 71 included studies, 22 were retrospective cohort studies, 5,20–40 36 were cross‐sectional studies, 6,10,19,41–73 seven were prospective cohort studies 74–80 and six were case‐control studies 81–86 (Supporting Information: Table ). Studies were conducted in a broad range of countries in Europe, North America and Asia, with the most numerous being from Denmark and the United States ( n = 14 each).…”
Section: Resultsmentioning
confidence: 99%